Highly efficient triazine/carbazole-based host material for green phosphorescent organic light-emitting diodes with low efficiency roll-off. Issue 12 (23rd January 2017) - Hu, Mingming; Liu, Yang; Chen, Yi; Song, Wenxuan; Gao, Lei; Mu, Haichuan; Huang, Jinhai; Su, Jianhua
Abstract : Two novel triazin/carbazole-based host materials were designed and synthesized, which demonstrated outstanding EL performance with maximum CE, PE and EQE of 69.3 cd A −1, 54.2 lm W −1 and 21.9%, respectively. Abstract : Two novel host materials, 3-(dibenzo[ b, d ]furan-4-yl)-9-(4, 6-diphenyl-1, 3, 5-triazin-2-yl)-9 H -carbazole (BFTC ) and 3-(dibenzo[ b, d ]thiophen-4-yl)-9-(4, 6-diphenyl-1, 3, 5-triazin-2-yl)-9 H -carbazole (BTTC ) were designed and synthesized. These two compounds exhibited excellent physical properties with high thermal stabilities and reasonable HOMO–LUMO energy levels. Both of them were applied to fabricate green phosphorescent organic light emitting devices (PhOLEDs) as host materials, and theBTTC based device demonstrated outstanding electroluminescence performance with a maximum current efficiency, maximum power efficiency and external quantum efficiency of 69.3 cd A −1, 54.2 lm W −1 and 21.9%, respectively, suggesting thatBTTC is a promising host for green PhOLEDs.